THE ROLE OF SOCIAL MEDIA AND MOBILE DEVICE ON E-COMMERCE IN MICRO SMALL MEDIUM ENTERPRISE IN MANADO - Tamuntuan, Santa .; Pangemanan, Sifrid S.; Tumewu, Ferdinand J. (Universitas Sam Ratulangi, 2018)
Abstract: Risk is the possibility that an undesired outcome-or the absence of a desired outcome disrupts a business process. Suppliers should be able to predict their possible risks that might be happened in their business. This study aims to identify supplier risk for coconut supplier and to give insights about the risk management. Identified perceived risks are classified as performance and relational risks managed by trust and control mechanisms. This is a qualitative study. Eight coconut suppliers had been interviewed for collecting data. Six supplier risks in performance risks and relational risks were identified. Relational risks include untrustworthy partner, unsatisfactory product quality, and delay in product delivery. Performance risks include vehicle damaged, lack of human resources, and shortage of raw materials. Â This research also identified trust-based mechanisms for supplier risks include farmer development and performance feedback. Control-based mechanisms for supplier risks include performance measurements and contractual agreement. The suppliers should try to implement the strategy of building trusts include goodwill trust and competence trust, and control such as output control, social control, and behavior control, simultaneously to help minimize relational and performance risks in the business.Â Keywords: supply chain management, supplier, risk, risk management.